Situation Report: Romania, 5 December 1975 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The Problem of the Young Writers Radio Bucharest Criticizes Deficiencies in Investments Plans to Produce Nuclear Fuel Romania at the UN: Disarmament and "Peace-Keeping" World Bank Approves New Loans to Romania Economic Relations with the US Ceausescu Pays Official Visit to Iran Former Party Leader Lucretiu Patrascanu's Birth Commemorated